2016
DOI: 10.1128/iai.00639-16
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Enteroids Model Guanylate Cyclase C-Dependent Secretion Induced by Heat-Stable Enterotoxins

Abstract: bEnterotoxigenic Escherichia coli (ETEC) causes ϳ20% of the acute infectious diarrhea (AID) episodes worldwide, often by producing heat-stable enterotoxins (STs), which are peptides structurally homologous to paracrine hormones of the intestinal guanylate cyclase C (GUCY2C) receptor. While molecular mechanisms mediating ST-induced intestinal secretion have been defined, advancements in therapeutics have been hampered for decades by the paucity of disease models that integrate molecular and functional endpoints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 43 publications
6
34
0
Order By: Relevance
“…At the molecular level, it is known that the downstream regulators of this pathway, cGMP and PKG, can enhance wild-type and mutant CFTR channel function and trafficking ( Golin-Bisello et al, 2005 ; Leier et al, 2012 ; Poschet et al, 2007 ; Vaandrager et al, 1997 ). Previous studies of mouse derived intestinal organoids showed that agonists of PKG are effective in enhancing CFTR-mediated organoid swelling, in the absence of agonists of the canonical regulation of CFTR, such as PKA ( Pattison et al, 2016 ; Picciotto et al, 1992 ; Seidler et al, 1997 ; Vaandrager et al, 1997 ). Our studies confirm the functional significance of this regulatory pathway in murine colon, and further, our findings suggest that PKG-mediated phosphorylation exerts a ‘priming’ effect on the canonical PKA-mediated activation of CFTR.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, it is known that the downstream regulators of this pathway, cGMP and PKG, can enhance wild-type and mutant CFTR channel function and trafficking ( Golin-Bisello et al, 2005 ; Leier et al, 2012 ; Poschet et al, 2007 ; Vaandrager et al, 1997 ). Previous studies of mouse derived intestinal organoids showed that agonists of PKG are effective in enhancing CFTR-mediated organoid swelling, in the absence of agonists of the canonical regulation of CFTR, such as PKA ( Pattison et al, 2016 ; Picciotto et al, 1992 ; Seidler et al, 1997 ; Vaandrager et al, 1997 ). Our studies confirm the functional significance of this regulatory pathway in murine colon, and further, our findings suggest that PKG-mediated phosphorylation exerts a ‘priming’ effect on the canonical PKA-mediated activation of CFTR.…”
Section: Discussionmentioning
confidence: 99%
“…Should the desired relief still not be achieved then newer prescription agents are available with different mechanisms. These agents include: lubiprostone, a chloride channel type 2 activator and prostaglandin analog 27 ; linaclotide, a GC-C agonist and analog of Escherichia coli heat-stable enterotoxin (STa) 28 , 29 ; and plecanatide, a GC-C agonist and analog of human uroguanylin. 9 Lubiprostone should be administered twice daily with food.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal organoid culture Small intestinal organoids derived from GC-C knockout mice were a generous gift from the laboratory of Scott Waldman and were isolated as described previously 21 . Organoids were maintained in 50 µl Matrigel droplets (Corning) in wells of a 24-well plate containing 650 µl IntestiCult mouse organoid growth medium (StemCell Technologies cat# 06005) at 37°C/5% CO2.…”
Section: Cellular Cgmp Assaymentioning
confidence: 99%